The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1002/da.20010
|View full text |Cite
|
Sign up to set email alerts
|

Actual and perceived memory deficits in individuals with compulsive hoarding

Abstract: Memory problems have been hypothesized to underlie compulsive hoarding behavior [Frost and Hartl, 1996: Behav Res Ther 34:341-350]. This study examined memory performance, memory confidence, and memory beliefs in 22 individuals with severe hoarding symptoms and 24 matched normal control subjects. Participants were administered two measures of learning and memory that required strategic planning and organization for successful performance: the Rey-Osterrieth Complex Figure Test (RCFT) and California Verbal Lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
126
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 148 publications
(145 citation statements)
references
References 38 publications
15
126
1
3
Order By: Relevance
“…Clearly, more research is needed to understand the precise functional significance of these findings but the negative correlations with dorsal prefrontal-striatal and parietal regions could reflect deficient emotional regulation mechanisms in compulsive hoarding 48 and would also be consistent with difficulties in planning, 49 another important feature of this syndrome. 50 Interestingly, only nonhoarding patients activated regions of the basal ganglia during symptom provocation and the degree of provoked anxiety correlated inversely with activation in this region in the entire sample (n = 29). Because the basal ganglia have been consistently implicated in non-hoarding OCD, our finding adds to the idea that the neural systems underlying compulsive hoarding are distinct from those implicated in other forms of OCD.…”
Section: Discussionmentioning
confidence: 87%
“…Clearly, more research is needed to understand the precise functional significance of these findings but the negative correlations with dorsal prefrontal-striatal and parietal regions could reflect deficient emotional regulation mechanisms in compulsive hoarding 48 and would also be consistent with difficulties in planning, 49 another important feature of this syndrome. 50 Interestingly, only nonhoarding patients activated regions of the basal ganglia during symptom provocation and the degree of provoked anxiety correlated inversely with activation in this region in the entire sample (n = 29). Because the basal ganglia have been consistently implicated in non-hoarding OCD, our finding adds to the idea that the neural systems underlying compulsive hoarding are distinct from those implicated in other forms of OCD.…”
Section: Discussionmentioning
confidence: 87%
“…The aim of this current study was thus to investigate the roles of attachment styles, attachment to objects, and anthropomorphism in predicting hoarding tendencies in a non-clinical population. As research has revealed sex differences in hoarding behaviours (Grisham et al, 2009;Hartl, Frost, Allen, Deckersbach, Steketee, Duffany et al, 2004), anthropomorphism (Neave et al, 2015) and in attachment styles (Del Giudice, 2011), the sample comprised males and females.…”
Section: Introductionmentioning
confidence: 99%
“…Research on beliefs about possessions suggests that these beliefs cluster into four basic subtypes: emotional attachment to possessions, poor memory confidence, exaggerated sense of responsibility for possessions, and desire for control over possessions (Frost, Hartl, Christian, & Williams, 1995;Hartl et al, 2004;Steketee, Frost, & Kyrios, 2003).…”
mentioning
confidence: 99%